O SILÊNCIO ESTÉTICO COMO ELEMENTO COMUNICACIONAL NA DIREÇÃO DE ARTE DO JOGO DIGITAL JOURNEY - Genciauskas, Sérgio Dassie (2013)
This research proposes the theoretical approach of silence as a comunicational element, as an element connected to the materiality of language, as a way able to produce narrative rhythm and edify projectual bases destinated to development and the implementation of art direction in a project to creat Journey, an independent eletronic game to the seventh generation videogames. The silence in Journey was observed as a composition element of language, in other words, as something that wasn t purposely said but could have produced some kind of communicational effect on the route of the narrative that was proposed to the plot. So, we discovered places and characters that compose the playful universe of this electronic game by the metaphore of silence, approaching narrative systems, technics of art direction and projectual relations established by this context. This is the central point of this project, translate the silence and its absences in a communicating element, transformer of players perception and sensibility by the narratives and the art direction of an artistic expression in shape of videogame.